2014
DOI: 10.1109/tlt.2014.2311807
|View full text |Cite
|
Sign up to set email alerts
|

Delving into Participants’ Profiles and Use of Social Tools in MOOCs

Abstract: This paper presents an in-depth empirical analysis of a nine-week MOOC. This analysis provides novel results regarding participants' profiles and use of built-in and external social tools. The results served to detect seven participants' patterns and conclude that the forum was the social tool preferred to contribute to the MOOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 8 publications
1
80
0
6
Order By: Relevance
“…The study of the academic engagement of students in Massive Open Online Courses (MOOCs) has already been tackled from different perspectives in the literature [1,2,6,7,14,17,18]. With this aim, various engagement indicators that describe different observable behaviors of MOOC students were employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the academic engagement of students in Massive Open Online Courses (MOOCs) has already been tackled from different perspectives in the literature [1,2,6,7,14,17,18]. With this aim, various engagement indicators that describe different observable behaviors of MOOC students were employed.…”
Section: Introductionmentioning
confidence: 99%
“…Another important finding is that the values of engagement indicators of many MOOC students decay over time often leading to dropping out [1,6,7,14,17,18]. As a consequence, the educational impact that the MOOC has in these disengaging learners is reduced, even if they do not eventually drop out.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the appearance of the first MOOC in 2008 (Connectivism and Connective Knowledge -CCK08), many authors have explored the benefits of using active pedagogies in this type of courses claiming that these pedagogies have a positive influence in various facets such as students' engagement [10]. The analysis of collaboration among students shows that social participation has a positive influence into student performance [1]. Some studies have focused on the students' preferences [11] finding that learners demand more opportunities for discussing in groups.…”
Section: Introductionmentioning
confidence: 99%
“…Twitter has been used to connect peers and share information, such as resources or comments on their personal and real-time status (Lin, Hoffman, & Borengasser, 2013). Facebook was found to have a greater impact than Twitter (Alario-Hoyos, Pérez-Sanagustín, Delgado Kloos, & Munoz-Organero, 2014;Salmon, Ross, Pechenkina, & Chase, 2015), and also more useful according to MOOC learners (Liu et al, 2016). MOOC learners also reported that the social networking tools had a positive impact on the social aspects of their learning process (Brownell & Swaner, 2010;Dodge & Kendall, 2004;Kassens-Noor, 2012) but they preferred to use the social medium to which they were already accustomed (Veletsianos & Navarrete, 2012).…”
Section: Tools For Interactionmentioning
confidence: 99%